2000
DOI: 10.1007/bf03401939
|View full text |Cite
|
Sign up to set email alerts
|

PLC-γ1 Signaling Pathway and Villin Activation Are Involved In Actin Cytoskeleton Reorganization Induced by Na+/Pi Cotransport Up-regulation

Abstract: IntroductionThe actin cytoskeleton participates in several cellular processes, including intracellular signaling, membrane trafficking, secretion, exoand endocytosis (1)(2)(3)(4)(5). Interactions between the actin cytoskeleton and the plasma membrane are thought to be important in many cellular events, including transport protein activity (6-9). The actin cytoskeleton may affect transport activity directly, by connecting transport proteins subunits to cytoskeletal elements Abstract Background: The brief incuba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
25
0
7

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 52 publications
(69 reference statements)
1
25
0
7
Order By: Relevance
“…These data are consistent with our previous reports demonstrating the association of tyrosine-phosphorylated villin with PLC-␥ 1 (1,18). 2 In cells expressing VIL/ANFM, PLC-␥ 1 formed a complex with the mutant villin protein, indicating that amino-terminal phosphorylation sites are not involved in PLC-␥ 1 binding. In contrast, in cells expressing either VIL/ACFM or VIL/AYFM, PLC-␥ 1 did not form a complex with villin.…”
Section: Tyrosine Phosphorylation Of Carboxyl-terminal Domain Of Villsupporting
confidence: 93%
See 4 more Smart Citations
“…These data are consistent with our previous reports demonstrating the association of tyrosine-phosphorylated villin with PLC-␥ 1 (1,18). 2 In cells expressing VIL/ANFM, PLC-␥ 1 formed a complex with the mutant villin protein, indicating that amino-terminal phosphorylation sites are not involved in PLC-␥ 1 binding. In contrast, in cells expressing either VIL/ACFM or VIL/AYFM, PLC-␥ 1 did not form a complex with villin.…”
Section: Tyrosine Phosphorylation Of Carboxyl-terminal Domain Of Villsupporting
confidence: 93%
“…More recent studies have established that examining epithelial cell migration in the context of proteins that are uniquely expressed in epithelial cells, including the actin-binding protein, villin is important to our understanding of this rather complex process (14). 2 We have demonstrated that overexpression of villin enhances cell migration (19). Likewise Athman et al (14) have demonstrated that villin enhances hepatocyte growth factor (HGF)-induced actin remodeling in epithelial cells.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations